Managing Expatriates - McNulty, Yvonne (Business Expert Press, 2013)
Ebook from IG Library ; Expatriation is a big topic, and is getting bigger. Over 200 million people worldwide now live and work in a country other than their country of origin. Tens of billions of dollars are spent annually by organizations that move expatriates around the world. Yet, despite the substantial costs involved, expatriation frequently results in an unsatisfactory return on investment (ROI), with little or no knowledge as to how to improve it. Why is this so? Drawing on more than a decade of expertise, research, and publications in top journals, the authors provide you real solutions to achieve more than a satisfactory ROI from expatriates--with rule number one being: Understand expatriates themselves. This book provides a practical 'insider's' guide that reveals why expatriates seek and accept international assignments; how they feel impacted by new forms of remuneration and other working conditions; how international assignments fit in with their longer-term career aspirations; and what complications arise in terms of their families. Whether you're a manager or consultant, inside you'll learn what modern-day global mobility is like (based on the authors' decade-long study with nearly four hundred expatriates and their managers, as well as over a hundred who were interviewed personally), how it is changing, and why now, more than ever, a hard-nosed ROI approach is necessary